Organizational readiness for building information modeling - Rachel Madeira Magalhães; Luiz Carlos Brasil de Brito Mello; Maria Aparecida Steinherz Hippert (Frontiers in Engineering and Built Environment, 2023)
Purpose – The main factor that leads organizations to implement Building Information Modeling (BIM) is customer demand. While this is a frequent topic in the BIM literature, few studies address BIM organizational readiness. Due to this gap in BIM implementation literature, this paper aims to understand what affects organizational BIM readiness and how the BIM readiness process occurs. Design/methodology/approach – The present paper adopts design science research as a methodological approach. A literature review examined 69 journal articles. The analysis focused on multiple theories, such as organizational readiness for change, adoption and diffusion of innovations and project management. Findings – By investigating BIM organizational readiness, this study presents a construct and a conceptual model for driving BIM readiness. Originality/value – This study can benefit researchers and organizations. The results presented may drive further research and discussions on the topic. But it is important to state that these results must be tested on real situations.